Transcendentalist Ideas in Works of Mexican-American Border Writers of 20th Century: Mary Hunter Austin and Rudolfo Anaya - T. V. Voronchenko; M. N. Fomina; E. V. Fyodorova (Научный диалог, 2024)
This article explores the embodiment and development of transcendentalist ideas from the 1830s to the 1850s in the works of Mexican-American border writers Mary Austin and Rudolfo Anaya, spanning the early and late 20th century. An analysis of the ideological and thematic content of their texts is conducted, highlighting key images and motifs. The study identifies the specific ways in which these authors perceive the relationship between humanity and nature, characterizing their views on social and personal harmony within the context of ethnocultural interaction. The research material includes popular sketches by Mary Austin (1868–1934) from the early 20th century, as well as the internationally renowned novels and essays of Rudolfo Anaya (1937–2020) from the latter third of the 20th century. The methodological foundation of this study is philosophical reflection, which enables the analysis of literary texts through the lens of philosophical concepts. The results indicate that transcendentalist ideas, rooted in the legacy of R. Emerson and H. Thoreau, are revitalized in the works of 20th-century Mexican-American border authors. In the prose of Mary Austin, a representative of early 20th-century Southwestern regional literature, there is a focus on the idyllic nature of human-nature relationships and the search for harmonious coexistence among members of society, which is envisioned through a pursuit of simplicity and “voluntary poverty.” Rudolfo Anaya’s transcendental vision of the world in his works from the latter third of the 20th century facilitates the transmission of an overarching theme of spiritual and moral self-improvement. According to the author, personal self-perfection is a crucial condition for achieving social harmony.